European Reference Network for Inherited and Congenital Anomalies Evidence-Based Guideline on Surgical Aspects of Necrotizing Enterocolitis in Premature Neonates - Hulscher, Jan; Irvine, Willemijn; Conforti, Andrea; Di Cesare, Antonio; Ichino, Martina; Sfeir, Rony; Madadi Sanjani, Omid; Strohm, Joanna; Hukkinen, Maria; Moschino, Laura; Norsa, Lorenzo; Kokešová, Alena; et al. (Neonatology, 2025)
Necrotizing enterocolitis (NEC) is a severe intestinal condition primarily affecting preterm neonates. It has a high mortality rate, particularly in infants with a birthweight of below 1,500 g or for those requiring surgical intervention. The European Reference Network for Inherited and Congenital Anomalies (ERNICA) has developed a clinical practice guideline to aid clinical decision-making pertaining to the surgical treatment and management of NEC in preterm neonates. This guideline was developed in accordance with the Guidelines 2.0 checklist and GRADE methodology. A multidisciplinary group of Europe's top experts collaborated with patient representatives to develop this guideline. After selecting critical points in care for which recommendations are required, a systematic review of the literature and critical appraisal of the evidence was performed. The Evidence to Decision framework was used as a guide to structure the consensus meetings and draft the recommendations. The panel developed seven recommendations and three good practice statements on the following topics: indications for surgery, peritoneal drainage, surgical technique, management of extensive NEC, enteral feeding, and neurodevelopmental outcomes in premature neonates with NEC. The certainty of evidence was graded as (very) low for most recommendations. However, the panel weighed up the benefits and harms in light of all relevant arguments and expert opinion. This guideline provides recommendations on caring for premature neonates with NEC. These recommendations can assist clinicians in their care decisions and can inform families on treatment options and relevant considerations. This guideline will be revised every 5 years to ensure it remains up to date.
Keywords: nekrotizující enterokolitida; Surgical management; Enterocolitis, Necrotizing; novorozenec nedonošený; enterální výživa; Clinical Decision-Making; Europe; medicína založená na důkazech; Premature; Evropa; novorozenec; lidé; Necrotizing enterocolitis; Humans; Infant, Newborn; Infant, Premature; European Reference Network for Inherited and Congenital Anomalies; Evidence-Based Medicine; klinické rozhodování; Enteral Nutrition; Guideline